IMPULSIVE BUYING DALAM BELANJA SECARA ONLINE PADA MAHASISWA - Zar, Sophia Akila (Brida Provinsi Jambi, 2024)
The rapid development of the internet has resulted in an increasing demand for internet services. Consequently, there has been a rise in the usage of e-commerce in Indonesia. Apart from serving as a source of information, the internet is now predominantly used for online shopping. Currently, there are numerous online shopping applications such as Shopee, Lazada, Tokopedia, Blibli, Bukalapak, and others. This trend can lead to impulsive buying behavior among consumers. Impulsive buying is characterized by sudden, unplanned purchases without prior consideration or product evaluation. The objective of this study is to determine the prevalence of impulsive buying among students at one of the public universities in Jakarta. This research adopts a descriptive qualitative approach to provide a deeper understanding of issues, events, and occurrences. The study uses purposive sampling involving three female students aged 18-24 years who have experience with online shopping. Data collection is carried out through semi-structured interviews conducted face-to-face.The findings indicate that students at one of the public universities in Jakarta exhibit impulsive buying behavior. Among the three subjects in this study, several types of impulsive buying behavior were identified, namely pure impulse buying, suggestion impulse buying, reminder impulse buying, and planned impulse buying. Each subject reported engaging in online shopping activities 3 to 5 times per month.